First report on the herpetofauna of Pulau Aur, Johor, West Malaysia - Grismer, L. Lee; Norsham, S. Yaakob; Liat, Lim Boo; Leong, Tzi Ming; Das, I.; Sosa, Roland A.; Grismer, Jesse L.; Crane, K. M.; Diaz, R. E.; Figueroa, S. V.; Ledbetter, C. A.; Newbold, S. C.; et al. (Centre for Herpetology, Madras Crocodile Bank Trust, 2001)
With the exception ofTweedie's (1983) account ofCalamaria lovii, published accounts on the herpetofauna of Pulau Aur, located 63 km off the south-east coast of peninsular Malaysia in the South China Sea did not exist prior to this report. The only species known from the island were based on the museum records ofLimnonectes blythii, Mabuya multi/asciata, Bronchocela cristatella, Gehyra mutilata, Varanus nebulosus and Ahaetulla prasina deposited in the Raffles Museum of Biodiversity Research. A short expedition to the island on 15-16 July 2001 yielded an additional 12 species, comprising 10 lizards and two snakes: Limnonectes blythii; Bronchocela cristatella; Cnemaspis cf. Nigridia; Cosymbotus platyurus; Cyrtodactylus consobrinus; Gehyra mutilata; Gekko monarchus; Hemidactylus frenatus; Dasia o/ivacea; Emoia atrocostata; Lygosoma bowring;;; Mabuya multi/asciata; Sphenomorphus scotophi/us; Varanus nebulosus; Varanus salvator; Ramphotyphlops cf. braminus; Calamaria lovii and Macropisthodon flaviceps.